KAFA'AH IN ISLAMIC MARRIAGE: CONCEPTUAL RECONSTRUCTION AND CRITICAL REVIEW OF CONTEMPORARY JURISPRUDENCE - Nasution, Hamzah (Qawwam : The Leader's Writing, 2025)
This study aims to explore and reconstruct the concept of kafa'ah in Islamic marriage law, which has often been misunderstood as a form of rigid and discriminatory social stratification. In fact, in classical Islamic jurisprudence, kafa'ah is intended as a principle of benefit to maintain marital harmony through the compatibility of partners in religious, moral, and social aspects. Using a qualitative approach and literature study methods, this study examines the views of four Islamic schools of jurisprudence and the dynamics of understanding kafa'ah in the contemporary context. The results show that kafa'ah is not a requirement for valid marriage, but rather a relative and contextual principle. The narrowing of its meaning due to the dominance of local culture and textualist interpretations has obscured the substance of justice in Islam. Therefore, a reinterpretation of kafa'ah based on maqāṣid al-shari'ah is necessary to realize the principles of justice, gender equality, and benefit in modern marriage practices.